Geospatial distribution of Hepatitis E seroprevalence in Nepal, 2021. - Chulwoo Rhee; Amy Dighe; Nishan Katuwal; Haeun Cho; Ramzi Mraidi; Dipesh Tamrakar; Jacqueline KyungAh Lim; Nimesh Poudyal; Il-Yeon Park; Deok Ryun Kim; Ritu Amatya; Rajeev Shrestha; et al. (PLoS Neglected Tropical Diseases)
Background Hepatitis E virus (HEV) causes acute jaundice and poses an important public health problem in low- and middle-income countries. Limited surveillance capacity and suboptimal access to diagnostics leads to under-reporting of HEV infections in affected countries, including Nepal. Serum antibodies against HEV are indicative of past infection. We analyzed existing samples from a nationally representative serosurvey to describe the geospatial distribution and factors associated with HEV seroprevalence in Nepal, as a proxy for infection. Methodology/principle findings A nationally representative cross-sectional serosurvey of 3,922 individuals ≥2 years old from 975 households spread across 65 wards throughout Nepal was conducted between November 2021 and January 2022. Bio-banked samples were tested for anti-HEV IgG. Seroprevalence and its 95% confidence interval were estimated by age, sex, ecological region, municipality type, and other waterborne-disease related risk factors. Bayesian geostatistical models were fitted to observed seroprevalence data and used to generate high-resolution maps of seroprevalence across Nepal. Available samples from 3,707 participants were tested for anti-HEV IgG, and 3,703 were used for final analysis. We found 20.8% (95% CI: 19.5-22.2) of participants had evidence of prior HEV infection. HEV seroprevalence increased with age, and was higher in males (23.5%, 95% CI: 21.5-25.5) than in females (18.6%, 95% CI: 16.9-20.3). Seroprevalence in hilly (28.9%, 95% CI: 26.6-31.2) and mountain (24.6%, 95% CI: 18.8-30.5) regions were significantly higher than in terai (14.2%, 95% CI: 12.7-15.8). While there was no significant difference between urban and rural populations, the predicted seroprevalence was highest in Kathmandu, the capital of Nepal, reaching seroprevalence of 50% in some selected area. No statistically significant differences were found for wealth quintile, water source, and toilet facility. Conclusions This study provides population-based serologic evidence that HEV is endemic in Nepal, with the greatest risk of infection in Kathmandu.